REFORMASI BIROKRASI PADA ORGANISASI MAKO KORPS MARINIR TNI AL MELALUI OPTIMALISASI PENATAAN DAN PENGUATAN MANAJEMEN SUMBERDAYA - Mochammad Sidik Rochullah; Daniel Guyana; Nico Christian (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
The renewal process in bureaucratic reform efforts is an important step to create good performance governance. One of the concrete steps that can be taken is optimizing the arrangement and strengthening the management of the Marine Corps Mako organization in the Indonesian Navy. In this study, bureaucratic reform efforts at the Marine Corps Mako were carried out through a literature review through a study of organizational behavior theory and evaluation of legislation. The results of this study indicate that reform efforts can be carried out through improving organizational structure in adaptability, restructuring, adaptation period, and optimizing organizational culture change. In addition, efforts that can be made in realizing reform are by evaluating organizational performance strategies, evaluating performance achievements, creating an environment that spurs opportunities for organizational development, to the realm of open communication and imposing strict sanctions to accelerate good bureaucratic reform